2019
DOI: 10.1063/1.5110973
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic device for on-chip isolation and detection of circulating exosomes in blood of breast cancer patients

Abstract: Tumor-derived circulating exosomes have been recognized as a promising biomarker source for cancer diagnosis via a less invasive procedure. The integration of isolation and detection of exosomes in routine clinical settings is still challenging. In this study, we developed a new microfluidic device for immunomagnetic separation and detection of blood exosomes in situ. The microfluidic device may empower the integration of target exosome analysis via high surface to volume ratios of immunomagnetic beads and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…It was shown that the platform can reliably target EVs highly accurate and specific, out of a background of complex media and in mixtures containing off‐target types of EVs. The obtained sensitivity is matching that of other ultrasensitive methods (comparison to selected EV capture methods in Table S1, Supporting Information), [ 74–81 ] spanning the whole range of physiological relevant EV concentrations. Furthermore, the lipid arrays were also demonstrated to retain the RNA (and thus probably the other biomaterial cargo) of EVs in the system, which shows the platforms potential to isolate RNA for downstream analysis.…”
Section: Discussionsupporting
confidence: 62%
“…It was shown that the platform can reliably target EVs highly accurate and specific, out of a background of complex media and in mixtures containing off‐target types of EVs. The obtained sensitivity is matching that of other ultrasensitive methods (comparison to selected EV capture methods in Table S1, Supporting Information), [ 74–81 ] spanning the whole range of physiological relevant EV concentrations. Furthermore, the lipid arrays were also demonstrated to retain the RNA (and thus probably the other biomaterial cargo) of EVs in the system, which shows the platforms potential to isolate RNA for downstream analysis.…”
Section: Discussionsupporting
confidence: 62%
“…Magnetic microbeads have been widely used for the separation of nucleic acids, protein, and EVs from clinic samples. [19][20][21][22][23][24][25][26][27] Although the microbeads allow fast and efficient collection of beads, the high material loss of microscale beads significantly quenches the resonance of the PC when the beads are immobilized. In contrast, the MNPs, whose diameter are much smaller than the operation wavelength, can be used to enhance the PC output without deteriorating the resonance mode.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 Alternatively, immunomagnetic methods using functionalized magnetic micro-and nanoparticles can enable efficient, fast, and specific extractions of EVs. [18][19][20][21][22][23][24][25][26][27] Following an extraction process, the EV samples need to be eluted and detected using an EV sensing approach. For example, nanoparticle tracking analysis can be used to obtain EVs' size and phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, the breast cancer cells-derived exosomes depicted a much higher MUC1 fluorescence, indicating the potential use of this method for further diagnosis of breast cancer. Chen et al [ 64 ] developed a new microfluidic device for immunomagnetic separation and detection of circulating exosomes in blood of breast cancer patients, able of on-chip isolation and detection of circulating exosomes within 1.5 h. A statistically significant increase ( p < 0.01) in EpCAM-positive exosomes was captured for breast cancer patients ( n = 10), when compared to healthy individuals ( n = 10). The device demonstrated high predicting accuracy for tumor exosomal markers with a sensitivity of 90% and a specificity of > 95%, providing a new automated platform to assist BC diagnosis.…”
Section: Ev-mediated Cancer Diagnosis For Six Specific Human Cancersmentioning
confidence: 99%